HUKUM PROGRESIF DAN PERKEMBANGAN TEKNOLOGI KECERDASAN BUATAN - Kusumawardani, Qur'ani Dewi (Veritas et Justitia, 2019)
Information technology in the era of Industrial Revolution 4.0 will become more sophisticated and increasingly influence the relationship between law and society. Law, in interaction with artificial intelligence and algorithms, will be expected in the future to provide quick and just answers to human problems.  It is also predicted that in settling disputes, artificial intelligence and algorithm will replace the role and function of lawyers and judges. This prediction of how artificial intelligence and algorithm will replace law’s societal function will be analyzed using the progressive law theory which perceived law to be subordinate to human interest.